Reactive Oxygen Species (ROS)-Responsive Nanomedicine for Solving Ischemia-Reperfusion Injury - Chen, Weiyu; Li, Deling (Frontiers in Chemistry, 2020)
Ischemia-reperfusion injury (IRI) is a severe condition for most organs, which could occur in various tissues including brain, heart, liver and kidney, etc.. As one of the major hazards, reactive oxygen species (ROS) is excessively generated after IRI, which causes severe damage inside tissues and further induces the following injury via inflammatory response. However, current medical strategies could not thoroughly diagnose and prevent this disease, eventually leading to severe sequelae by missing the best time point for therapy. In the past decade, various nanoparticles that could selectively respond to ROS have been developed and applied in IRI. These advanced nanomedicines have shown efficient performance in detecting and treating a series of IRI (e.g., acute kidney injury, acute liver injury and ischemic stroke, etc.), which are well summarized in the current review. In addition, the nano-platforms (e.g., anti-IL-6 antibody, rapamycin and hydrogen sulfide delivering nanoparticles, etc) for preventing IRI during organ transplantation have also been included. Moreover, the development and challenges of ROS-responsive nanomedicine are systematically discussed for guiding the future direction.